Machining parametric study on the natural fiber reinforced composites: A review. (June 2022) - Mahakur, Vijay Kumar; Bhowmik, Sumit; Patowari, Promod Kumar
Nowadays, the utilization of natural fiber reinforced composite has increased frequently. These natural fibers have significant features like low cost, renewable, and, more importantly, biodegradable in nature, making them to be utilized for various industrial sectors. However, the massive demand for natural fiber reinforced composites (NFRC), forces them to be machined and operated, which is required for countless areas in multiple industries like automotive, marine, aerospace and constructions. But before obtaining the final shape of any specimen, this specimen should come across numerous machining processes to get the desired shape and structure. Therefore, the present review paper focused on the various aspects during conventional and unconventional machining of the NFRC. It covers the work by exploring the influence of all input variables on the outcome produced after machining the NFRC. Various methodologies and tools are also discussed in this article for reducing the machining defects. The machining of the NFRC is found as a challenging task due to insufficient interlocking between the matrix and fibers, and minimum knowledge in machining characteristics and appropriate input parameters. Thus, this review is trying to assist the readers to grasp a basic understanding and information during the machining of the NFRC in every aspect.